ESTUDO DAS TECNOLOGIAS CRIATIVAS PARA CONFORTO ACÚSTICO - Stein De Arruda, Pâmela; Rieger, Cássia; Vargas Barbosa Dos Santos, Jéssica Tuane; Valdiero, Antonio Carlos; Da Silva Dos Santos, Claudio; Tassotti Marchesan, Fernanda (Salão do Conhecimento, 2015)
Resumo